2022
DOI: 10.1021/acs.iecr.1c04185
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Modeling of CO2 Separation Systems with Soluble, Redox-Active Capture Species

Abstract: Electrochemical approaches hold promise for energy-efficient and modular carbon dioxide (CO2) separation systems that can make direct use of renewably generated electricity. Here, we employ a thermodynamic modeling approach to estimate the upper performance bounds of CO2 separation processes that use soluble, redox-active capture species. We contemplate the impact of tunable molecular and electrolyte properties on the thermodynamic and faradaic efficiencies of four characteristic system configurations. We find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 57 publications
0
40
0
Order By: Relevance
“…The use of ethanol as an additive to TCQ-based eCCC systems provides enhanced O 2 stability, which is essential for practical eCCC. The batch-capture experiments performed with a closed H-cell system is similar to a 3-stage cathodic absorption system, where the redox carrier is reduced or “activated” in the presence of CO 2 before being pumped over to the anodic cell where it is oxidized to release bound CO 2 . , The minimum thermodynamic requirement for this type of redox-carrier eCCC system can be estimated from the Δ E between the half-wave potentials of the carrier in the presence of its dilute CO 2 inlet stream (in this case, flue gas at 10% CO 2 v/v) and of its concentrated outlet stream (100% CO 2 ). ,,, Sample calculations and further discussion can be seen in the Supporting Information (Tables S7 and S8). Cyclic voltammograms of TCQ in the presence and absence of 2 M ethanol under 10 and 100% CO 2 are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The use of ethanol as an additive to TCQ-based eCCC systems provides enhanced O 2 stability, which is essential for practical eCCC. The batch-capture experiments performed with a closed H-cell system is similar to a 3-stage cathodic absorption system, where the redox carrier is reduced or “activated” in the presence of CO 2 before being pumped over to the anodic cell where it is oxidized to release bound CO 2 . , The minimum thermodynamic requirement for this type of redox-carrier eCCC system can be estimated from the Δ E between the half-wave potentials of the carrier in the presence of its dilute CO 2 inlet stream (in this case, flue gas at 10% CO 2 v/v) and of its concentrated outlet stream (100% CO 2 ). ,,, Sample calculations and further discussion can be seen in the Supporting Information (Tables S7 and S8). Cyclic voltammograms of TCQ in the presence and absence of 2 M ethanol under 10 and 100% CO 2 are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…We want to direct the readers’ attention to a recent study by Brushett et al. that utilized a thermodynamic modeling approach to estimate the upper performance bounds of EMCC with soluble, redox-active organic CO 2 carriers ( Clarke et al., 2022 ). The authors considered four system configurations and observed competing trends between the thermodynamic and faradaic efficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…This expression for the Faradaic efficiency upper bound aligns with several previous works. 124,125,126 Considering an example system with a 10% CO2 stream (typical concentration from a coal-fired power plant flue gas) 23,28 and the following constant parameters ([R] T = 1 M, KH = 0.175 M/atm, 𝐾 2(R) ≪ 1, 𝑞 = 1), a 𝐾 1(R 𝑛− ) value of at least 6.3 x 10 2 is required to obtain ≥ 90% of the maximum Faradaic efficiency predicted with eq. 9.…”
Section: Introductionmentioning
confidence: 99%
“…To further assess this tradeoff between system energy requirements and Faradaic efficiency, Clarke et al defined a combined efficiency metric to highlight molecular properties (such as 𝐾 1(R 𝑛− ) ) that may be effective to adequately balance this tradeoff. 126 Their work also explores how these effective properties are dependent upon other system properties, such as system configuration.…”
Section: Introductionmentioning
confidence: 99%